Pathways of soil organic matter formation in agroecosystems as influenced by litter chemistry, root depth and aggregation - Fulton-Smith, Sarah E., author; Cotrufo, M. Francesca, advisor; Paustian, Keith, committee member; Ojima, Dennis, committee member; Fonte, Steven, committee member (Colorado State University. Libraries, 2024)
Soils contain more carbon (C) than any other terrestrial reservoir, and the increase of these C stocks has been targeted as a potential climate solution globally. Agroecosystems play a critical role in our ability to provide these climate solutions through increasing soil organic matter (SOM). There is significant potential for SOM accrual in agroecosystems due to the degradation of SOM typically observed in these systems. One promising approach to increasing soil C sequestration is through the selection of deep-rooted crops, such as Sorghum bicolor. However, significant questions remain about root inputs' ability to contribute to SOM in order to balance the greenhouse gas (GHG) lifecycle of a bioenergy feedstock. My dissertation aims to answer some of these questions as well as to propose a framework to integrate the study of SOM formation from crop inputs with soil aggregate structure. Bioenergy has the potential to emit fewer GHGs than other fuel sources, such as fossil fuels, yet there are some emissions during the transportation production of bioenergy feedstocks and fuels that could be offset by soil C sequestration. However, in annual bioenergy systems, aboveground biomass is typically removed from the system, meaning roots are the primary source of OM available to return to the soil. However, roots and shoots may differ significantly in their ability to contribute to SOM due to differences in litter chemistry. In Chapter 2, I conducted a field incubation to understand how sorghum root versus leaf litter, as influenced by their contrasting chemistry, affect the formation and stabilization of SOM. Using unique soil-biomass microcosms to incubate root or leaf litter in topsoil (0-30 cm) for 19 months in the field, I traced the fate of litter decomposition products by combining stable 13C and 15N isotope labeling with extensive separation of physical soil fractions, free or within different aggregate structures. I found that roots, which were lower quality than leaves, decomposed more slowly but contributed more efficiently to total SOM formation than leaves. However, leaves contributed more to the stable SOM pool (i.e. associated to minerals) while roots contributed more to less stable fractions (i.e. light particulate organic matter). Additionally, sorghum is known to produce roots to a depth of 2 meters. There is limited understanding of how roots deeper in the soil (e.g., below 30 cm) lead to SOM formation and stabilization. In Chapter 3, I used the same microcosm approach as in Chapter 2, with roots that were incubated up to a 90 cm depth to better understand how depth influences the ability of roots to contribute to the formation of SOM and what role aggregates play in this process. Results of this study showed that differences in root decomposition dynamics with depth resulted in greater accrual of root litter C in more stable mineral associated SOM pools in the surface depth while there was slower decomposition and greater accrual in the less stable particulate organic matter fractions in the deep soil. Interestingly, most of the stable fraction was recovered within soil aggregates, particularly microaggregates. The results of these experiments emphasized the important role of microaggregates in modulating SOM dynamics. In Chapter 4, I used the information gleaned from Chapters 2 and 3 as well as advances in the SOM research community to speculate on the role of aggregation, specifically microaggregates, in moderating SOM formation by presenting a conceptual framework that integrates aggregates within our current understanding of particulate and mineral associate SOM dynamics. Overall, my dissertation addresses fundamental questions about our ability to increase SOM levels and resulting soil C accrual through the production of a deep-rooted crop through a field incubation. At the same time, I have connected these relevant results to the broader SOM research community by presenting a novel conceptual model that advances our current SOM framework. My hope is that this will be a valuable contribution to the field and spark discussion and future research.
Keywords: deep soil; soil aggregation; soil organic matter; root litter decomposition; carbon sequestration; soil carbon